Linear Regression Analysis of NURJA Water Mineral Purchases at NJMART Paiton Probolinggo: Linear Regression Analysis of NURJA Water Mineral Purchases at NJMART Paiton Probolinggo - Nadhiroh, Anis Yusrotun; Putri, Anin Dhita Mey P; Annur, Annur Farida; siti, Siti Romla (Universitas Nahdlatul Ulama Surabaya, 2024)
This study aims to analyze the factors that influence the purchase of NURJA Water mineral water using the linear regression method. The background of this study is based on the growth of the mineral water industry in Indonesia which shows a positive trend, as well as the need for a deeper understanding of the factors that influence consumer purchasing decisions. The independent variables analyzed include price, quality, packaging, and promotion, while the dependent variable is the amount of NURJA Water mineral water purchases. The research data was obtained through a survey of NURJA Water consumers and analyzed using statistical software to determine the relationship between these variables. The results of the analysis show that price and product quality have a significant influence on purchasing decisions, while packaging and promotion also contribute but with a smaller influence. These findings indicate that competitive pricing strategies and improving product quality are the main keys to increasing sales of NURJA Water mineral water. In addition, attractive packaging and effective promotions are still needed to support consumer purchasing decisions. This study provides valuable insights for NURJA Water in formulating more targeted marketing strategies that can be implemented to strengthen their position in the mineral water market.